Analisis Makna Tuturan dalam Ritual Pangara Ana pada Masyarakat Wewewa Di Kabupaten Sumba Barat Daya, Nusa Tenggara Timur - Malo, Flavianus Mario; Kamuri, Paulus Ama; Bessu, Lidia Vera (Lembaga Bale Literasi, 2025)
Sumba culture, especially the pangara ana tradition, plays an important role in the Wewewa community, which has been practiced for generations and continues to develop to this day. This study focuses on the meaning of speech in the Pangara Ana ritual among the Wewewa community in Southwest Sumba. The urgency of this study is marked by the lack of knowledge among the younger generation to understand the meaning of speech in the form of words (traditional language) found in the Pangara Ana ritual among the Wewewa community in Southwest Sumba. The purpose of this study is to analyze the speech in the Pangara Ana ritual among the Wewewa community in Southwest Sumba. The research method used is a qualitative descriptive method with an ethnographic approach. Data collection techniques include observation, in-depth interviews, and documentation studies. Data analysis techniques include data reduction, categorization and coding, contextual analysis, presentation, and conclusion drawing. The results of the study show that lexically, Pangara Ana is not chosen randomly, but has a special meaning related to the hopes of the family, history, circumstances of birth, or characteristics desired by the Wewewa community. In contextual terms, names serve as a vital form of symbolic communication, reflecting their perspectives on life, the environment, and the spiritual realm. In religious terms, names carry meaning and power, and by involving ancestors in the naming process, the child is spiritually recognized as part of the tribe or kabissu